KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING DALAM HUBUNGAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG - Meftahudin Meftahudin; M. Trihudiyatmanto (JURNAL EKOBIS DEWANTARA, 2023)
Repurchase intention is a repurchase activity that is carried out more than once or several times for a product. This study aims to identify the effect of product quality on repurchase intention with customer satisfaction as an intervening variable on the scarlett beauty brand in the PPTQ Al-Asy'ariyyah Kalibeber student block, Mojotengah, Wonosobo. This research consists of product quality variable (X), repurchase intention variable (Y), and customer satisfaction variable (Z). The sample in this study were Scarlett users in the PPTQ Al-Asy'ariyyah Kalibeber student block, Mojotengah, Wonosobo, who were taken as many as 107 respondents. This research is the result of a survey on the PPTQ Al-Asy'ariyyah student block using a questionnaire measured using a Likert scale and using a non-probability sampling technique using a purposive sampling method. The statistical method uses Structural Equation Modeling (SEM) analysis and the mediation test uses the Sobel test tool. The results of the study show that: (1) There is a positive influence on product quality on repurchase intention with a CR value of 4.320 and a probability of 0.000. (2) Customer satisfaction mediates product quality on repurchase intention with a Sobel test value of 2.403. (3) There is a positive influence of product quality on customer satisfaction with a CR value of 2.971 and a probability of 0.003. (4) There is a positive influence of customer satisfaction on repurchase intention with a CR value of 3.280 and a probability of 0.001.